PENENTUAN FOOT OF SLOPE (FOS) PADA WILAYAH POTENSI LANDAS KONTINEN EKSISTENSI NEGARA KESATUAN REPUBLIK INDONESIA - Eka Djunarsjah; Obedh Try Samekto Sidabutar (Universitas Pendidikan Indonesia (UPI), 2021)
According to the United Nations Convention on the Law of the Sea as a result of the 3rd conference (UNCLOS III) held in 1973-1982, the continental shelf is defined as an area on the seabed and subsoil that is outside the territorial sea, as long as its natural prolongation from land, to the outermost edge of the continental margin, or up to a distance of 200 nautical miles from the baselines. The coastal State may also propose a continental shelf of more than 200 nautical miles (extended continental shelf) based on the position of the foot points of the continental slope. In this study, the method for determining the position of the foot points of the continental slope begins with identifying the morphology of the slopes around the boundaries of the Exclusive Economic Zone, then based on a global bathymetry map, the coordinates of the foot points of the slope are determined, then plotted into foot of slope lines. The results of this study are 19 coordinates of points indicated as the foot of the eurapic rise slope in the southwest region of Sumatra Island, which can then be used to determine the boundaries of the extended continental shelf.Keywords: Continental shelf, Coordinate of foot of slope, Extended foot of continental slope,UNCLOS III